INVESTIGATION OF THE AIR POLLUTION TOLERANCE INDEX (APTI) USING SOME PLANT SPECIES IN AHVAZ REGION - A. Gholami; A. Mojiri; H. Amini (Journal of Animal and Plant Sciences, 2016)
Air pollution is one of the main environmental problems in many cities around the world. Controlling this kind of pollution is more complex than other environmental challenges. Many plants can absorb and save some of the environmental pollutants through their leaves. Therefore, air pollution tolerance index (APTI) was tested in polluted and blank areas in six plant species,namely, Conocarpus, Myrtus, Prosopis, Eucalyptus, Ziziphus, and Lebbek, which are abundant in the Ahvaz region during 2014. Dust deposition on leaf surfaces was determined to observe the extent of particulate deposition. The highest and the lowest deposition rates were observed in Myrtus (maximum 80.3 g.m-2 in polluted site) and Lebbek (minimum 10.7 g.m-2 in blank site), respectively. The APTI was calculated to be 4.97 for Prosopis, 5.25 for Ziziphus, 6.24 for Lebbek, 6.59 for Conocarpus, 6.77 for Eucalyptus and 7.80 for Myrtus in blank site and 4.57 for Prosopis, 4.82 for Ziziphus, 5.79 for Lebbek, 5.84 for Eucalyptus, 6.30 for Conocarpus and 7.21 for Myrtus in the polluted areaat the end of study. The APTI showed that Myrtus is resistant to plant pollution, whereas Prosopis is sensitive to plant pollution. In addition, the results of assessment of the above mentioned index showed that plants with higher APTI can be used as reducers of pollution and plants with lower APTI can be used to measure air pollution.
Keywords: Air pollution tolerance index; Total chlorophyll content; Relative water content; Ahvaz region